Pengaruh Mutu Pelayanan Dan Mutu Pemasaran Di Toko Fashion Aziziah Pare Terhadap Kepuasan Pembeli Perspektif Etika Bisnis Islam - Moch. Uzeir Mustaqfirin (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2022)
This study aims to determine the effect of service quality and marketing quality on buyer satisfaction at Aziziah Pare fashion store from the perspective of Islamic business ethics, and which is more influential between service quality and marketing quality on buyer satisfaction at Aziziah Pare fashion store from the perspective of Islamic business ethics. The method in this research is a type of survey research with the approach used in this research is descriptive-quantitative. For data analysis techniques using multiple linear regression testing and correlation and the coefficient of determination (R2). Then in data collection techniques using interviews, observation, and questionnaires. The conclusion of this study is that service quality has a significant influence on buyer satisfaction which can be explained by the sig value. 0.004 <0.05. And marketing quality has a big impact on buyer satisfaction which can be explained by the sig value. 0.002 <0.05. For the more dominant variable between service quality and marketing quality on buyer satisfaction. Considering the results of the previous analysis, it is clear that service quality (score 0.004) dominates marketing quality (score 0.002).